The effect of anti-cellulite massage with thermoactive oil on the skin affected by cellulite in different women age groups - Liovinaitė, Gabrielė; Stungienė, Lina (Applied Scientific Research, 2022)
The article analyzes the effect of anti-cellulite massage with thermoactive oil on the skin affected by cellulite in women of different ages. Changes in skin condition assessment are presented – cellulite stage, skin temperature, skin color, skin elasticity and volume. The graphs show the most significant changes according to the different age groups of women. Key words: cellulite, anti-cellulite massage, oil.